2013
DOI: 10.3324/haematol.2012.064642
|View full text |Cite
|
Sign up to set email alerts
|

Impaired clearance of apoptotic cells leads to HMGB1 release in the bone marrow of patients with myelodysplastic syndromes and induces TLR4-mediated cytokine production

Abstract: Excessive pro-inflammatory cytokine production in the bone marrow has been associated with the pathogenesis of myelodysplastic syndromes. We herein investigated the involvement of toll-like receptors and their endogenous ligands in the induction/maintenance of the inflammatory process in the marrow of patients with myelodysplastic syndromes. We evaluated the expression of toll-like receptors in marrow monocytes of patients (n=27) and healthy controls (n=25) by flow-cytometry and also assessed the activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 44 publications
3
51
1
Order By: Relevance
“…39,48 TLR4 is the most widely studied receptor for HMGB1-mediated inflammation. 17,20 However, our results showed that most CLL samples have absent or weak TLR4 expression, and TLR4 blockade by the neutralizing antibody failed to prevent NLC differentiation. RAGE and TLR9 are ubiquitously expressed in CLL cells and are highly expressed in stromal-like cells in the CLL microenvironment.…”
Section: Org Fromcontrasting
confidence: 42%
See 2 more Smart Citations
“…39,48 TLR4 is the most widely studied receptor for HMGB1-mediated inflammation. 17,20 However, our results showed that most CLL samples have absent or weak TLR4 expression, and TLR4 blockade by the neutralizing antibody failed to prevent NLC differentiation. RAGE and TLR9 are ubiquitously expressed in CLL cells and are highly expressed in stromal-like cells in the CLL microenvironment.…”
Section: Org Fromcontrasting
confidence: 42%
“…44,45 Increased circulating HMGB1 is found in some cancers, including malignant peritoneal mesothelioma 46 and myelodysplastic syndromes. 20 Higher circulating HMGB1 is associated with worse clinical outcomes, and plasma samples with higher concentrations of HMGB1 (.150 ng/mL) in our study were from relapsed or progressive CLL patients and are correlated with Ten untreated and 6 relapsed CLL peripheral mononuclear cells were stored at 280°C and lysed directly from the pellets. Fifty micrograms of proteins was loaded onto each lane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by guest www.bloodjournal.org From myeloid dysplasia. 32 Together with previously reported evidence of dyserythropoiesis attributable to loss of RPS14, 7,8 and dysmegakaryopoiesis attributable to loss of miR-145/146a, 12,13 the combined loss of RPS14, miR-145/146a, and mDia1 may recapitulate the pathogenesis of trilineage dysplasia in MDS with del(5q).…”
Section: Discussionmentioning
confidence: 84%
“…4,7 In addition, the BM plasma concentration of HMGB1, a nuclear DAMP and TLR4 ligand, was significantly increased in MDSs (n 5 55) compared with controls (n 5 11) (P 5 2.6 3 10 23 ) ( Figure 2C), consistent with intracellular DAMP release upon cytolysis. 26,27 Moreover, S100A9 and HMGB1 transcripts were upregulated 104.5-fold and 1.5-fold in MDSs, respectively, compared with normal donors (Figure 2D-E). Further, flow cytometry analyses of phenotypically distinct hematopoietic lineages confirmed a corresponding increase in intracellular S100A9 in MDS stem cells and progeny ( Figure 2F-G).…”
Section: The Alarmin S100a9 Initiates Pyroptosismentioning
confidence: 97%